SOCIALIZATION AND EDUCATION ON THE APPLICATION OF ORGANIC FERTILIZER AND PLANT PESTICIDE IN ARIPAN VILLAGE, SOLOK REGENCY - Dewi Jayagma ilham; Nurhaita; Chrisnawati; Aulia Meyuliana; Friza Elinda; Renfiyeni (PAKDEMAS : Jurnal Pengabdian Kepada Masyarakat, 2025)
The Aripan Village in X Koto Singkarak District, Solok Regency is suboptimal soil characterized by a dominant clay texture, high bulk density, low porosity, and inadequate organic matter content. This condition is exacerbated by community cultivation practices that still rely on chemical fertilizers and synthetic pesticides, potentially reducing soil quality, suppressing soil biological activity, and increasing the risk of environmental pollution. This activity aims to enhance farmers' knowledge and skills regarding the benefits and techniques for applying organic fertilizers and botanical pesticides as environmentally friendly alternatives to conventional inputs. The methods used include material delivery, interactive discussions, and hands-on practice in making compost from organic waste. In addition, participants were introduced to various local plants such as papaya leaves, paitan, and babadotan, which have potential as botanical pesticide ingredients. The results showed a significant increase in community understanding regarding the function of organic fertilizers, the negative impacts of long-term chemical fertilizer use, and the importance of botanical pesticides in safer pest control. Participants were able to make compost with the right composition and understand how to apply botanical pesticides. Overall, this activity succeeded in raising awareness and encouraging the adoption of organic technology towards a healthier, more sustainable agricultural system that is in line with the local potential of Aripan Village.